Security schemes based on conditional privacy-preserving vehicular ad hoc networks - Mahmood A. Al-shareeda; Mohammed Anbar; Murtadha A. Alazzawi; Selvakumar Manickam; Iznan H. Hasbullah (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Recently, vehicular ad hoc networks (VANETs) have been garnering significant inter-est from the people involved in transportation field. Nowadays automotive manufactur-ers have already supplying vehicles with multitude of road sensors that provides many useful characteristics. VANET communication not only offers the drivers and passen-gers with the various safety related services but also provides a wide range of valuable applications. However, the inherent openness of the wireless communication medium used by VANETs exposes vehicles to various security and privacy issues. Researchers have proposed many security schemes to solve the issues mentioned above for the widespread deployment of VANETs. However, these schemes failed to fulfill all as-pects of security and privacy requirements. Besides, these schemes have not provided the performance parameters such as computation and communication costs. The pri-mary emphasis of this paper is on the taxonomy of security schemes based conditional privacy-preserving with respect to strengths and limitations. Besides, a comparison be-tween these schemes related to the model of security and privacy requirements, attacks, and performance parameters is provided. Finally, this paper critically reviews the re-lated works by taking into consideration the design and development of all VANETs security and privacy schemes, this paper could serve as a guide and reference.